OPTIMUM MATCHING OF KINEMATIC PARAMETERS OF CUTTING COAL GANGUE SHEARE - DING Fei; LI BinBin; ZHOU WenChao (Jixie qiangdu)
Based on the coal rock material nonlinear theory and rigid flexible coupling multi-body system dynamics theory,the optimal matching of the parameters of shearer was studied.Using Ansys/LS-DYNA software, the coupling simulation model was established for shearer drum with gangue coal, the coal extraction process run down by three to the spiral drum three to force and torque, the volume of coal and rock was cut out.The relationship between the motion parameters and load fluctuation coefficient, cut down the coal volume, cutter safety coefficient, cutting energy consumption, coal loading rate and productivity were analyzed using these results; Using the MATLAB optimization toolbox, the load fluctuation coefficient, cut down the coal volume, cutter safety coefficient, cutting ratio energy consumption, coal loading rate and productivity as the goal function, the multi-objective optimization equation is established for motion parameters of shearer spiral drum. The results show that: when the roller speed is 86.3 r/min, traction speed is 3.87 m/min, the motion parameters of Shearer to achieve optimal matching.In the optimal state,the load fluctuation coefficient is 0.272; the cutting energy consumption ratio is 0.784 kw·h/m~3; cutter safety coefficient is 2.035; the loading rate is 57.132%; the maximum productivity is 3.025 t/min.